GAMBARAN KETANGGUHAN DIRI (RESILIENSI) PADA MAHASISWA TAHUN PERTAMA FAKULTAS KEDOKTERAN UNIVERSITAS RIAU - Sherty Amelia; Enikarmila Asni; Daviq Chairilsyah (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Resilience is an individual ability to face a difficult situations. First year students have to deal with new environment which sometimes difficult. The purpose of this study was to find out the resilience level of first year students in Medical Faculty of Riau University. This study used descriptive cross-sectional method. The population are students in the Faculty of Riau University batch 2013. Samples of this research were 119 students. This research used a questionnaire based on the Reivich & Shatte's Resilience Theory. From the result, it was found that the majority (89,07%) students are in intermediate level of resilience. The aspects of resilience in order from highest to lowest level are empathy, emotion regulation, achievement, self-efficacy, optimism, analyzes the causes of the problem, and control of impulse.